Clinical implementation of artificial intelligence in neuroradiology with development of a novel workflow-efficient picture archiving and communication system-based automated brain tumor segmentation and radiomic feature extraction - Aboian, Mariam; Bousabarah, Khaled; Kazarian, Eve; Zeevi, Tal; Holler, Wolfgang; Merkaj, Sara; Cassinelli Petersen, Gabriel; Bahar, Ryan; Subramanian, Harry; Sunku, Pranay; Schrickel, Elizabeth; Bhawnani, Jitendra; et al. (Frontiers in Neuroscience, 2022)
Purpose: Personalized interpretation of medical images is critical for optimum patient care, but current tools available to physicians to perform quantitative analysis of patient’s medical images in real time are significantly limited. In this work, we describe a novel platform within PACS for volumetric analysis of images and thus development of large expert annotated datasets in parallel with radiologist performing the reading that are critically needed for development of clinically meaningful AI algorithms. Specifically, we implemented a deep learning-based algorithm for automated brain tumor segmentation and radiomics extraction, and embedded it into PACS to accelerate a supervised, end-to-end workflow for image annotation and radiomic feature extraction. Materials and Methods: An algorithm was trained to segment whole primary brain tumors on FLAIR images from multi-institutional glioma BraTS 2021 dataset. Algorithm was validated using internal dataset from Yale New Haven Health (YHHH). A UNETR was embedded into Visage 7 (Visage Imaging, Inc., San Diego, CA) diagnostic workstation. PyRadiomics (Harvard Medical School, Boston, MA) was natively embedded into Visage 7 for feature extraction from the brain tumor segmentations. Results: UNETR brain tumor segmentation took on average 4 seconds and the median DSC was 86%, which is similar to published literature but lower than the RSNA MICCAI challenge 2021. Finally, extraction of 106 radiomic features within PACS took on average 5.8±0.01 seconds. The extracted radiomic features did not vary over time of extraction or whether they were extracted within PACS or outside of PACS. The ability to perform segmentation and feature extraction before radiologist opens the study was made available in the workflow. Opening the study in PACS, allows the radiologists to verify the segmentation and thus annotate the study. Conclusions: Integration of image processing algorithms for tumor auto-segmentation and feature extraction into PACS allows curation of large datasets of annotated medical images and can accelerate translation of research into development of personalized medicine applications in the clinic. The ability to use familiar clinical tools to revise the AI segmentations and natively embedding the segmentation and radiomic feature extraction tools on the diagnostic workstation accelerates the process to generate ground-truth data.